29 Feasibility of using a defibrillator to provide real-time and post-event feedback to paramedics on the quality of their CPR. (26th April 2019) - Smith, K; Dyson, K; Stub, D; Magnuson, N; Anastasopoulos, K; Bernard, S
Abstract : Background: Ambulance Victoria aimed to improve paramedic CPR performance by introducing audio-visual CPR feedback via a defibrillator with accelerometer-based technology and detailed debriefs post event. Method: We conducted an evaluation assessing the feasibility of using a defibrillator to provide real-time and post-event feedback to paramedics on the quality of their CPR. The pilot was conducted over a 6 month period between the 17th June 2017 and 17th December 2017. Results: Ambulances participating in the trial arrived first at 234 out-of-hospital cardiac arrests (OHCA). Of these cases, teams voluntarily used the CPR Feedback Pads for 85 (36%) OHCA, however case data was only available for 70 cases. The majority (77%) of paramedics who used the CPR Feedback device found it easy to apply with the defibrillator pads, with little to no disruption to standard CPR performance. The recommended chest compression depth (>5 cm) and rate (100–120 compressions per minute) were achieved for half of cases (51% for both). The median chest compression fraction (84%) was above the recommended standard of >80%. Overall, only 26% of paramedics who received real-time feedback were able to achieve all three CPR Quality Standards. When compared to perceived performance, this statistic differed significantly, as the majority (70%) of paramedics believed their CPR was already of good quality. Most paramedics reported that they found the post-event feedback helpful (74%). Conclusion: Although utilization rates were low for the CPR Feedback device, the mismatch between perceived and actual performance highlights the need for such feedback. Conflict of interest: None. Funding: None.